NEURAPRO: A multi-centre RCT of omega-3 polyunsaturated fatty acids versus placebo in young people at ultra-high risk of psychotic disorders - Medium-term follow-up and clinical course - Nelson, B (2020)
10.1038/s41537-018-0052-x